ELABORATION AND CHARACTERIZATION OF ZNO NANOSTRUCTURE THIN LAYERS - Ghougali, M.; Belahssen, O.; Chala, A. (University of Eloued جامعة الوادي, 2018)
ZnO thin films have been deposited onto the glass substrates by chemical spray pyrolysis technique at 500°C. The effect of precursor molarity and crystallite size on structural, optical and electrical properties has been studied. The XRD lines of the deposited ZnO were enhanced with increasing precursor molarity due to the improvement of the layers crystallinity. It was shown that the average of the crystallite size of the deposited thin layers was calculated using Debye–Scherrer formula and found in the range between 30 and 95 nm. A strong c-axis preferred orientation is observed for all of the samples. As the growth temperature increases, the crystallite orientation of the ZnO (002) plane is not changed, but the full width at half maximum gets smaller. The optical properties have been discussed in this work. The transmittance (T) and the absorbance (A) were measured and calculated. Band gap energy is considered one of the most important optical parameter, therefore measured and found ranging 3.285 eV. The increase of the electrical conductivity to maximum value of 0.0695 (Ω cm)−1 can be explained by the increase in carrier concentration of the films. A good electrical conductivity of the ZnO thin film is obtained due to the electrically low sheet resistance. ZnO can be applied in different electronic and optoelectronic applications due to its band gap, high transparency and good electrical conductivity.
Séminaire National Sur Laser Solaire Et Matériaux ElOeued 5-6 Février 2018
Keywords: Thin films ZnO; Optical properties; DRX; Electrical properties